Preservation of a rural and cultural landscape : insights from the multinomial and error components logit model - Gomes, Lina Lourenço (2013)
The present paper uses the discrete choice experiments to elicit visitors’preferences for a hypothetical preservation program of the main attributes of the Alto Douro Wine Region, an evolving rural and cultural landscape, classified by UNESCO as world heritage site. The paper compares the performance of the multinomial logit model, relying on the independence assumption between the choices made by the same respondent, with the error components logit model that explicitly considers the panel data structure. There is evidence that the utility of participating in a preservation program is positively determined by the income level and by the status of ADW’ world heritage list. Moreover, the utility is negatively influenced by household size andby the distance between the residence and the ADW.